Selected aspects of burnout among physiotherapists - Kurzeja, Piotr; Szurmik, Tomasz; Prusak, Jarosław; Kuziel, Agata; Mrozkowiak, Mirosław (Journal of Education, Health and Sport, 2018)
Introduction and purpose of the work Occupational burnout may be the result of the long-term exposure to stress, in particular through the use of ineffective remediation. Such a burden may also be treatment and care of a sick person. Physiotherapists belong to a group that can also be burdened with stress, accompanying them in working with sick people and in need of care. An outpatient and stationary physiotherapist is exposed to various dangerous and harmful factors, physical and psychosocial loads, i.e. a multitude of occupational hazards. The aim of the study was to find out about the problem of occupational burnout among physiotherapists and selected factors that may affect this situation, taking into account the nature of the work. Material and method The research was conducted on a group of 50 physiotherapists: 25 worked in centers where patients were permanently resident (ZOL, DPS), 25 worked with outpatients (NZOZ). The method was a diagnostic survey, the technology research was a survey, and the research tool was an original questionnaire consisting of 30 questions. Results A sense of lack of recognition appeared more often in physiotherapists working in a stationary method, whereas people working with outpatient patients more often confirmed fair treatment by the management. Conclusions Physiotherapists working with stationary patients are more likely to report situations that may affect the burnout process, among others: a feeling of lack of recognition, unfair treatment of staff by the management, stress at work.